Solving the challenge of the blood-brain barrier to treat infections caused by Trypanosoma evansi: Evaluation of nerolidol-loaded nanospheres in mice - Baldissera M.D. (2017)
Copyright © Cambridge University Press 2017.Despite significant advances in therapies against Trypanosoma evansi, its effective elimination from the central nervous system (CNS) remains a difficult task. The incapacity of trypanocidal drugs to cross the blood-brain barrier (BBB) after systemic administrations makes the brain the main refuge area for T. evansi. Nanotechnology is showing great potential to improve drug efficacy, such as nerolidol-loaded nanospheres (N-NS). Thus, the aim of this study was to investigate whether the treatment with N-NS was able to cross the BBB and to eliminate T. evansi from the CNS. High-performance liquid chromatography revealed that N-NS can cross the BBB of T. evansi-infected mice, while free nerolidol (F-N) neither the trypanocidal drug diminazene aceturate (D.A.) were not detected in the brain tissue. Polymerase chain reaction revealed that 100% of the animals treated with N-NS were negatives for T. evansi in the brain tissue, while all infected animals treated with F-N or D.A. were positives. Thus, we concluded that nanotechnology improves the therapeutic efficacy of nerolidol, and enables the transport of its active principle through the BBB. In summary, N-NS treatment can eliminate the parasite from the CNS, and possesses potential to treat infected animals.